The Trespassing Cyborg: Technology, Nature, and the Nation in Wild Wild West - Kötzing, Stephen (Aspeers: Emerging Voices in American Studies, 2011)
Drawing on the studies by Leo Marx and Henry Nash Smith, this paper analyzes the 1999 Western comedy Wild Wild West as negotiating the boundaries of nature and technology. Set in 1869 and taking place mostly in the American West, the film depicts a clash of civilization/technology and wilderness/nature and, with its resolution of the conflict, attests to the ideal of the ‘American Garden.’ Furthermore, Wild Wild West is infused with ideas related to westward expansion and Frederick Jackson Turner’s frontier thesis. By partially revising and thereby affirming and refitting the frontier myth for the twenty-first century, the film can be interpreted to reimagine the American nation. In terms of terrorist threats and the fear of weapons technology possibly falling into ‘wrong’ hands, the beginning of this century presents the United States with hazards very similar to the ones which Jim West and Artemus Gordon, the film’s protagonists, have to face as they set out to defend the nation.
Keywords: Wild Wild West (Film); Frontier Myth; Western; American Garden